The diagnosis and treatment of 56 cases of breast hamartoma: a single-center analysis and a review of the literature - Su, Hao; Bai, Caiyun; Fan, Zhimin; Wu, Di; Qu, Fengjiang (Frontiers in Medicine, 2025)
IntroductionTo analyze and summarize the clinical and pathological features of breast hamartoma to enhance clinicians’ awareness of this rare and benign lesion of the breast.MethodsWe retrospectively described the clinical data, imaging results, and pathological findings of 56 patients with breast hamartoma who underwent surgical treatment at the First Hospital of Jilin University between January 2005 and December 2020, and summarized the features. Additionally, a literature review was conducted using the PubMed database for clinical reports on breast hamartoma and analyzed them.ResultsThis study included 56 female patients. Preoperative ultrasound revealed round or elliptical heterogeneous echoes with clear boundaries: hypoechoic in 35 cases (63%), iso-echoic in 8 cases (14%), hyperechoic in 1 case (2%), mixed echo in 9 cases (16%), slightly strong echo in 1 case (2%), and uneven echo of fat in 2 cases (4%). Mammography was performed in 33 cases, revealing clear and dense shadows in 20 cases (61%) and dense shadows on the outer edges in 16 cases (48%). The excised masses were solid, with light yellow and gray cut surfaces. Pathological analysis identified ducts and fibrous tissue, with intra-tumoral fat content ranging from 10 to 90%.ConclusionBreast hamartoma is prevalent among perimenopausal women and is characterized by ultrasound and radiography; surgical intervention remains the primary treatment with a good prognosis.